Re‐evaluation of women's nutritional needs, knowledge and behaviours in a tertiary maternity service: are we meeting women's needs yet?. Issue 3 (29th January 2013) - Wilkinson, Shelley A.; Walker, Alice; Tolcher, Debbie
Abstract: Aim: The aim of the present study was to assess changes in nutritional awareness, knowledge and behaviours of women following nutrition service changes, implemented after a 2008 survey, in a Queensland Maternal Health Hospital. Methods: In 2011, 356 antenatal and 138 postnatal women were surveyed for seven weeks. Results were compared with those from a previous survey in 2008 of a similar cohort of 309 antenatal and 102 postnatal women. Results: The cohorts were similar on most demographic, anthropometric and pregnancy characteristics. Approximately half were primiparous and over one‐third had a body mass index of >25 kg/m 2 . Similar proportions of women accessed the nutrition services both years (4.9%, 9.6%) and felt the service met their needs (94–100%). In both survey years, women had poor diet quality, despite identifying healthy eating as a high priority. While similar proportions reported receiving written information (63.8% vs 69.6%), women surveyed in 2011 rated its appearance more favourably (3.7 ± 0.9 vs 3.9 ± 0.8; P < 0.001), found it useful (3.7 ± 0.9 vs 3.9 ± 0.8; P = 0.003) and knew of nutrition services available (10.5% vs 27.5%; P < 0.001), compared with the 2008 cohort. In 2011, women had lower gestational weight gain (12.8 ± 5.2 kg vs 14.5 ± 6.3 kg; P = 0.04) and more knew correct gestational weight gain guidelines ( P = 0.005) compared with the 2008 cohort. Conclusion: Evidence‐based service changes at the Maternal Health Hospital have effected positive change in women's gestational weight gain and service awareness and ratings. However, targeted, intensive interventions may be required to improve diet quality and manage gestational weight gain to ensure optimal pregnancy outcomes.